Effect of temperature on the stability of nickel sulfide reduced graphene oxide nanocomposite counter electrode in quantum dot-sensitized solar cells - Kharboot, Layla Haythoor; Mohd Najib, Abdillah Sani; Abu Bakar, Tuty Asma; Nordin, Norhuda Hidayah; Eka Putra, Andi Erwin; Altaf, Ataf Ali; Fadil, Nor Akmal (Springer Nature, 2026)
Quantum dot-sensitized solar cells (QDSSCs) are equipped with counter electrodes (CEs) based on reduced graphene oxide (rGO) and nickel sulfide (NiS/rGO). A hydrothermal method performed at 150 °C with variable reaction times (5, 10, and 15 h) was used to synthesize NiS/rGO CEs and evaluate their electrocatalytic activity and stability by exposing them to varying conditions at 25, 40, 60, and 80 °C for 100 h. Electrochemical performance was assessed through cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and Tafel polarization. Results showed that NiS/rGO 5 h exhibited superior electrocatalytic activity, achieving a significantly higher current density. CV results showed that NiS/rGO 5 h generated the highest current density of 112.4 mA/cm2 at 80 °C (Pt = 8.1 mA/cm2), and lower charge-transfer resistance (Rct values, 3.6 Ω cm2 at 80 °C than (Pt = 674.4 Ω cm2).The high performance was attributed to the dominance of β-NiS phase. Additionally, the nanocomposites demonstrated strong mechanical adhesion and stability under prolonged exposure to elevated temperatures. This study highlights the potential of NiS/rGO nanocomposites as cost-effective and efficient alternatives to Pt for improved QDSSC performance